Response based identification of critical wave scenarios - Clauss, Günther F.; Klein, Marco; Soares, Carlos Guedes; Fonseca, Nuno (Volume 2: Structures, Safety and Reliability, 2012)
In the last years the identification and investigation of critical wave sequences regarding offshore structure responses became one of the main topics in the ocean engineering community. Thereby the area of interest covers the entire field of application spectra at sea - from efficient and economic offshore operations in moderate sea states to reliability as well as survival in extreme wave conditions. For most cases, the focus lies on limiting criteria for the design, such as maximum global loads, maximum relative motions between two or more vessels or maximum accelerations, at which the floating structure has to operate or to survive. These criteria are typically combined with a limiting characteristic sea state (Hs, Tp) or a rogue wave. For the investigation of offshore structures as well as the identification of critical wave sequences, different approaches are available - most of them are based on linear transfer functions as it is an efficient procedure for the fast holistic evaluation. But, for some cases the linear method approach implies uncertainties due to nonlinear response behavior, in particular in extreme wave conditions. This paper presents an approach to these challenges, a response based optimization tool for critical wave sequence detection. This tool, which has been successfully introduced for the evaluation of the applicability of a multi-body system based on the linear method approach, is adjusted to a nonlinear task - the vertical bending moment of a chemical tanker in extreme wave conditions. Therefore a nonlinear strip theory solver is introduced into the optimization routine to capture the nonlinear effects on the vertical bending moment due to steep waves acting on large bow flares. The goal of the procedure is to find a worst case wave sequence for a certain critical sea state. This includes intensive numerical investigation as well as model test validation.